1993
DOI: 10.2169/internalmedicine.32.484
|View full text |Cite
|
Sign up to set email alerts
|

Increased RAHA Titer and Interleukin-6 Levels in the Synovial Fluid in a Patient with Polymyalgia Rheumatica.

Abstract: Wereport a patient with polymyalgia rheumatica (PMR) accompanied by an increased Rheumatoid Arthritis Hemagglutinin Test (RAHA)titer and interleukin-6 level in the synovial fluid. A 60-year-old female was admitted because of polymyalgia, a body temperature of 39.2°C, and an erythrocyte sedimentation rate increased to 94 mm/h. Since a muscle biopsy failed to show a specific finding, she was diagnosed as PMR.The titer of RAHAand the interleukin-6 level were increased only in the synovial fluid; prednisolone trea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…Although the pathogenesis of this disorder remains unknown, IL-6 has been identified as the only cytokine occurring at a consistently high level in patients with the active form of the disease; it is recognized as the most sensitive indicator of disease activity and course. 107,109111,135 IL-6 was also reported to be elevated in the synovial fluid 136 and in the muscle interstitial concentrations of cytokines. 137 IL-6 inhibition with TCZ may thus constitute a novel strategy for the treatment of PMR.…”
Section: Additional Applications Of Tocilizumab For Other Immune-medimentioning
confidence: 96%
“…Although the pathogenesis of this disorder remains unknown, IL-6 has been identified as the only cytokine occurring at a consistently high level in patients with the active form of the disease; it is recognized as the most sensitive indicator of disease activity and course. 107,109111,135 IL-6 was also reported to be elevated in the synovial fluid 136 and in the muscle interstitial concentrations of cytokines. 137 IL-6 inhibition with TCZ may thus constitute a novel strategy for the treatment of PMR.…”
Section: Additional Applications Of Tocilizumab For Other Immune-medimentioning
confidence: 96%
“…In patients with PMR, infiltration of macrophages and CD45RO + T cells and the expression of adhesion molecules, such as VCAM-1 and ICAM-1, have been observed in the synovia of the shoulders (2,3). It has also been reported that interleukin 6 levels are increased in the shoulder joints (4,5). One study found a decrease in CD4 + CD25 high Foxp3 + regulatory T cells and an increase in pro-inflammatory T cell subsets, such as Th1 and Th17, in the peripheral blood of PMR patients (6).…”
Section: Introductionmentioning
confidence: 97%